The Correlation of Habits of Mind and Attitude towards Science in Scientific Literacy - Surya, Veronica Junior Ayme; Sunarti, Titin (Universitas Halu Oleo, 2021)
Several influential factors influence the ability of scientific literacy skills. This study aims to (1) describe the capability of scientific literacy, habits of mind, and attitudes towards science (2) identify the correlation habits of mind and scientific literacy, (3) identify the correlation attitude towards science and scientific literacy, and (4) identify the correlation of habits of mind and attitude towards science in scientific literacy on dynamic fluid. This study used 50 students from SMA Negeri 4 Surabaya. This study is an ex-post-facto study that uses scientific literacy test instruments by dynamic fluid topic, habits of mind questionnaires, and attitudes towards science questionnaires to collect data. The data obtained were analyzed using inferential statistic-analysis with simple regression, multiple regression, simple correlation, and multiple correlation tests. The results of the study obtained (1) capability of habits of mind, attitude towards science and scientific literacy of students on the dynamic fluid are in the high criteria (2) there is a moderate positive correlation between habits of mind and scientific literacy with a value of r = 0.574 (3) there is a weak positive correlation between attitudes towards science and scientific literacy with a value of r = 0.352 (4) there is a strong positive correlation of habits of mind and attitude towards science in student scientific literacy on dynamic fluid. Besides, habits of mind and attitude towards science contributed 37.6% to student scientific literacy. This study implies that the habits of mind and attitude towards science play an essential role in improving students' scientific literacy skills.